(untitled) (International Conference on Modern Science and Scientific Studies, 2025)
This article explores the fundamental components of terminology and language, emphasizing their critical role in effective communication across various fields. It examines key linguistic elements such as terminology, lexis, semantics, syntax, morphology, pragmatics, and register, highlighting how each contributes to clarity and precision in both everyday and specialized contexts. The article also addresses the importance of consistency in the use of terminology and the impact of lexical choice and context on meaning. By understanding these core elements, readers can enhance their communication skills and better navigate professional and academic discourse.